(untitled) - Okuda, Seiiti (Tokyo, 1941)
Contents: I. Japanese outlook toward industrial arts; II. Range of japanese industrial arts; III. Development of japanese industrial arts; IV. Foreign Influnence on their development; V. Characteristics of japanese industrial arts
Keywords: Nghệ thuật trang trí,Decorative arts; Nhật Bản,Japan